1999
DOI: 10.1037/0735-7028.30.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Complaints, malpractice, and risk management: Professional issues and personal experiences.

Abstract: As psychologists strive to affect human welfare in a positive way, their greater exposure and responsibilities have led to worry about potential malpractice lawsuits and state licensing board complaints. Are psychologists at increasing risk for litigation? What steps can they take to alleviate the stress and worry? A survey of licensed psychologists (N = 284) explored professional awareness, personal experiences, and practice activities related to complaints, malpractice lawsuits, and risk management. Professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 28 publications
1
46
0
2
Order By: Relevance
“…Thomas (2005) speculates: BThe abundance of recent publications and commensurate awareness undoubtedly contribute to psychologists' fears of becoming the subject of a complaint^(p. 426). After attending a seminar on risk management, many attendees will over-react and sense that the risk of a complaint is greater than is the reality (Montgomery, Cupit, & Wimberley, 1999;Van Horne, 2004).…”
Section: Ulnerability To Allegations Of Wrongful Conductmentioning
confidence: 98%
“…Thomas (2005) speculates: BThe abundance of recent publications and commensurate awareness undoubtedly contribute to psychologists' fears of becoming the subject of a complaint^(p. 426). After attending a seminar on risk management, many attendees will over-react and sense that the risk of a complaint is greater than is the reality (Montgomery, Cupit, & Wimberley, 1999;Van Horne, 2004).…”
Section: Ulnerability To Allegations Of Wrongful Conductmentioning
confidence: 98%
“…Although there is some indication that psychologists may believe the risk of a licensing complaint is greater than is actually the case (Montgomery et al 1999;Van Horne 2004), the anxiety and stress that is experienced are real and portend to impose psychological and physical harm or damage. In fact, Thomas (2005) speculates: "The abundance of recent publications and commensurate awareness undoubtedly contribute to psychologists' fears of becoming the subject of a complaint" (p. 426).…”
Section: Effects Of Psychological Injurymentioning
confidence: 94%
“…Licensing boards generally must review any formal written complaint about a psychologist's services or behavior. Montgomery, Cupit, and Wimberly (1999), in a study of Texas psychologists, found that licensing complaints and malpractice actions alleging wrongdoing in the context of a parenting plan evaluation were second in frequency only to allegations of sexual misconduct.…”
Section: Licensing Board Complaintsmentioning
confidence: 96%
“…Where injury was alleged to have occurred, the complaining party must still prove that the alleged injury is caused by the psychologist's breach of the standard of care and not by some other variable. Even though the risk of being held liable may be reasonably limited, the emotional and financial costs of malpractice litigation are burdensome (Montgomery, Cupit, & Wimberly, 1999).…”
Section: Civil Remedies and The Question Of Immunitymentioning
confidence: 99%